CHINESE CULTURE REPRESENTATION IN THE FILM TANDA TANYA BY HANUNG BRAMANTYO - Monica Darmawan; Yohan Yusuf Arifin (Celt: A Journal of Culture, English Language Teaching and Literature, 2026)
Indonesia is a country rich in cultural diversity, for example, Chinese culture that has long been rooted in the country. Chinese culture has been in the socio-cultural life of Indonesia, making it quite widely studied in various films. Tanda Tanya is a film that raises the issue of diversity in Indonesia. In this film, Chinese culture is one of the important elements in it. The representation of Chinese culture in the film depicts a symbol of diversity that simultaneously shows the participation of Chinese culture in shaping the multicultural identity of Indonesia. This study aims to reveal the meaning of the representation of Chinese culture in the film Tanda Tanya through the behavior of the characters, visualization, conversations between the characters presented, and examine how the film Tanda Tanya constructs the meaning of the interaction between Chinese culture and local culture. The type of research used in this study is descriptive qualitative with a semiotic analysis approach proposed by Roland Barthes, and strengthened by Stuart Hall's representation theory and Harsojo's views on culture. The data collection technique used in this study is the listening and recording technique. The results of the study show that the representation of Chinese culture in the film is quite diverse. This representation encourages the understanding that Chinese culture can interact and coexist harmoniously in Indonesia's multicultural society.